MOLECULAR IDENTIFICATION OF A DESTRUCTIVE PHYTOPATHOGENIC FUNGUS IN TOMATO FIELDS OF IRAN - Parissa Taheri; Atena Pourmahdi (European Scientific Journal, ESJ, 2013)
The necrotrophic fungus Rhizoctonia solani is one of the most important, soil-borne pathogens with a wide host range. This pathogen is the casual agent of crown rot, root rot and damping off in tomato producing areas. The purpose of this research was to characterize the Rhizoctonia spp. isolates obtained from tomato at different taxonomic levels, to investigated genetic diversity and pathogenicity of these isolates Sampling was carried out in the main tomato growing regions of Khorassan-Razavi Province during 2011-2012. Morphological characteristics such as the hyphal diameter and conformation, presence of dolipore septum, the number of nuclei per hyphal cell, the size of monilioid cells and sclerotia were investigated for the 39 Rhizoctonia spp. isolates obtained from tomato plants. Additionally, 7 R. solani isolates obtained from potato were investigated in this research. In total, 46 Rhizoctonia spp. isolates were obtained which consisted of 41 R. solani isolates and 5 isolates belonged to binucleate Rhizoctonia spp. Morphological characterization revealed variability among the isolates. The anastomosis grouping on slide was primarily used for determining anastomosis groups (AGs) and intraspecific groups (ISGs). The PCR-RFLP method was used to confirm the identified AGs and determine the ISGs. In this method. The ITS1, 5.8S, and ITS2 regions of rDNA were amplified using the species-specific primers of R.solani including RS1 and RS4. Then the PCR product was restricted using various restriction enzymes such as Mun I, Mse I, Hinc II and Ava II. The AG and ISG of each isolate was determined by comparing the restriction pattern of each R. solani isolate obtained in this study with the pattern of standard isolates. The PCR- RFLP analysis revealed that R. solani isolates belonged to AG2-1, AG3 PT, AG4 HG I, and AG4 HG II with the number of 4, 15, 13, and 9 isolates respectively.